Belief functions : theory and applications : 4th International Conference, BELIEF 2016, Prague, Czech Republic, September 21-23, 2016, Proceedings /: theory and applications : 4th International Conference, BELIEF 2016, Prague, Czech Republic, September 21-23, 2016, Proceedings. (2016) - Unknown
No abstract available